make use of the graphs of f and g to graph f g h(x) = (f + g)(x).

(Graph portions with shut endpoints.) h x f g x make use of the graphs of f and g to graph h(x) = (f + g)(x). (Graph portions with shut endpoints.)

As h(x) = (f+g)x

Therefore, h(x) = f(x) + g(x)

Refer the affixed sheet

* many thanks

Option :- h(x)= (4+g)(x) = f(x)+g(2) 3 2. 2 3 4 3 Therefore, we shall simply take f & g values at different a to graph h(x) hlo) = f(0)+7(0) = 2-1 > 1 h(!) = f(1)+ g(1) > 3+0 3 h (2) = f(2)+9(2) > +0.5 > 1.5 h (3) = f(3) + g(3) > 2+0 > 2 Therefore, Graph should be .. 1 3 h(x) 2 Solution 7 x บ 1 2 3 4